Phase I pilot study of Wilms tumor gene 1 peptide‐pulsed dendritic cell vaccination combined with gemcitabine in pancreatic cancer. Issue 4 (9th March 2015) - Mayanagi, Shuhei; Kitago, Minoru; Sakurai, Toshiharu; Matsuda, Tatsuo; Fujita, Tomonobu; Higuchi, Hajime; Taguchi, Junichi; Takeuchi, Hiroya; Itano, Osamu; Aiura, Koichi; Hamamoto, Yasuo; Takaishi, Hiromasa; et al.
Abstract : This study aimed to evaluate the feasibility of and immune response to Wilms tumor gene 1 ( WT1 ) peptide‐pulsed dendritic cell vaccination combined with gemcitabine (DCGEM) as a first‐line therapy among patients with advanced pancreatic cancer. Ten HLA‐A*2402 patients were treated with WT1 peptide‐pulsed DC vaccination (1 × 10 7 cells) on days 8 and 22 and gemcitabine (1000 mg/m 2 ) on days 1, 8 and 15. Induction of a WT1‐specific immune response was evaluated using the delayed‐type hypersensitivity (DTH) skin test, interferon‐γ enzyme‐linked immunospot and HLA tetramer assays, along with assays for various immunological factors. DCGEM was well‐tolerated, and the relative dose intensity of gemcitabine was 87%. Disease control associated with a low neutrophil/lymphocyte ratio was observed in all three patients with DTH positivity; it was also correlated with a low percentage of granulocytic myeloid derived suppressor cells in the pretreatment peripheral blood ( P = 0.017). Patients with liver metastases and high levels of inflammatory markers such as C‐reactive protein and interleukin‐8 (IL‐8) showed poor survival even though a WT1‐specific immune response was induced in them. WT1 peptide‐pulsed DCGEM is feasible and effective for inducing anti‐tumor T‐cell responses. Our results support future investigations for pancreatic cancer patients with non‐liver metastases and favorable immunological conditions. This trial was registered with the University hospital Medical Information Network (UMIN) Clinical Trials Registry (http://www.umin.ac.jp/ctr/ number: UMIN‐000004855). Abstract : WT1 peptide‐pulsed DCGEM is feasible and effective for inducing anti‐tumor T‐cell responses. Our results support future investigations for pancreatic cancer patients with non‐liver metastases and favorable immunological conditions.